0.1°C accuracy ICO temperature sensor with segmentation algorithm. Issue 11 (1st May 2018) - Li, Jing; Zhou, Pengfei; Hu, Yuanbin; Wang, Zhaochi; Wei, Yi; Li, Chengze; Wu, Kejun; Ning, Ning
Abstract : A real‐time temperature detection circuit with 0.1°C accuracy is presented. The temperature sensor is composed by a current controlled oscillator (ICO). Its oscillating frequency is proportional to the temperature but independent with the power supply. The frequency change will be digitised by a counter and thus realise the temperature detection. The detection accuracy is limited by the linearity of ICO. In order to improve temperature detection accuracy, a temperature segmentation algorithm is proposed. The temperature sensor is implemented with 0.18 μm CMOS technology and the core area is 0.023 mm 2 . The power consumption of the proposed sensor is 0.3 mW with 1.8 V supply. Experimental results show that this sensor can detect the temperature from −40 to 125°C with 0.1°C accuracy and the detection error is within ±0.8°C.